Osborn wave in ECG in elderly patient with so-called urban hypothermia - Paweł Kiciński; Monika Szymańska; Jarosław Niedziałek; Beata Lis; Andrzej Prystupa (Kazimierz Wielki University, 2016)
Kiciński Paweł, Szymańska Monika, Niedziałek Jarosław, Lis Beata, Prystupa Andrzej. Osborn wave in ECG in elderly patient with so-called urban hypothermia. Journal of Education, Health and Sport. 2016;6(8):206-209. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.60084 http://ojs.ukw.edu.pl/index.php/johs/article/view/3748       The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.07.2016. Revised 25.07.2016. Accepted: 12.08.2016.     Osborn wave in ECG in elderly patient with so-called urban hypothermia   Paweł Kiciński1, Monika Szymańska2, Jarosław Niedziałek2, Beata Lis3, Andrzej Prystupa3   1Department of Family Medicine, Medical University of Lublin, Poland 2Individual Medical Practice, Lublin, Poland 3Department of Internal Diseases, Medical University of Lublin, Poland     Abstract The Osborn wave is a characteristic twisting at the termination of the QRS complex visible at the J point. Its presence is most commonly associated with hypothermia, electrolyte imbalance, primary cardiac disorders or CNS pathologies. A case of a 78-year-old male with Osborne wave caused by deep hypothermia is presented.   Key words: electrocardiography, hypothermia, Osborn wave.